2012
DOI: 10.1525/mp.2014.31.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Musical Activity Tunes Up Absolute Pitch Ability

Abstract: Absolute pitch (AP) is the ability to identify or produce pitches of musical tones without an external reference. Active AP (i.e., pitch production or pitch adjustment) and passive AP (i.e., pitch identification) are considered to not necessarily coincide, although no study has properly compared these abilities. Using a novel computerized pitch adjustment test, we investigated active AP ability in musicians with and without AP (ages 18-43). We found a significant correlation between active and passive AP indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 49 publications
0
33
0
1
Order By: Relevance
“…They also tend to be worse at identifying the pitch of vocal tones than other instruments (Vanzella & Schellenberg, 2010), an effect that may be related to the vocal generosity effect (Hutchins, Roquet, & Peretz, 2012), in which all listeners tend to be worse at determining the tuning of vocal pitches. There is also a general effect for AP possessors to be better at identifying white-key, rather than black-key pitches (which tend to be less frequent; Dohn, Garza-Villarreal, Ribe, Wallentin, & Vuust, 2014;Miyazaki, 1988), again highlighting the role of experience in AP ability. The relevance of any and all of these categories varies between AP possessors, and AP itself can vary from being highly automatic to barely present.…”
Section: T He Act Of Imitating a Vocal Pitch Whilementioning
confidence: 92%
“…They also tend to be worse at identifying the pitch of vocal tones than other instruments (Vanzella & Schellenberg, 2010), an effect that may be related to the vocal generosity effect (Hutchins, Roquet, & Peretz, 2012), in which all listeners tend to be worse at determining the tuning of vocal pitches. There is also a general effect for AP possessors to be better at identifying white-key, rather than black-key pitches (which tend to be less frequent; Dohn, Garza-Villarreal, Ribe, Wallentin, & Vuust, 2014;Miyazaki, 1988), again highlighting the role of experience in AP ability. The relevance of any and all of these categories varies between AP possessors, and AP itself can vary from being highly automatic to barely present.…”
Section: T He Act Of Imitating a Vocal Pitch Whilementioning
confidence: 92%
“…After listening to the detuned symphony, musicians with AP made transposed answers, suggesting that the AP template can be (presumably temporarily) affected by the concurrent experience. Another study reported that the precision of AP perception was positively correlated with daily musical experience (Dohn et al, 2014 ), suggesting that the AP template indeed seems to be refreshed and retuned by daily musical experience. Note that these studies (Van Hedger et al, 2013 ; Dohn et al, 2014 ) used a fairly liberal definition of AP (i.e., >68% of a maximum score) according to a large-scale study (Athos et al, 2007 ).…”
Section: Absolute Pitch Memory Vs Absolute Pitch Categorizationmentioning
confidence: 99%
“…While a number of neuroimaging studies reported the possible involvement of several brain regions (Schlaug et al, 1995 ; Keenan et al, 2001 ; Ohnishi et al, 2001 ; Itoh et al, 2005 ; Bermudez et al, 2009 ; Oechslin et al, 2009 ; Wilson et al, 2009 ; Loui et al, 2011 ; Jäncke et al, 2012 ; Dohn et al, 2014 ; Elmer et al, 2015 ), the neural mechanisms of AP remain unclear. Novel studies provide behavioral and neuroimaging evidence (Van Hedger et al, 2013 , 2015a , b , 2016 ; Kim and Knösche, 2016 , 2017 ), questioning previously assumed characteristics of AP behaviors and underlying neural structures and functions.…”
Section: Absolute Pitchmentioning
confidence: 99%
“…AP might be conceptualized in direction of the memory system as complex ability [22,30] or musical auditory skill [124] with the note categorization performance strengthened depending on short-term and long-term memory resources, that continually influence AP performance. The frequency of regular hearing the accurate timbres, pitch classes of octaves determine the speed and accuracy of AP note identification based on specific auditory experiences [22,196], with the possibility of AP improvement during active musical instrument playing [72,314].…”
Section: Absolute Pitch As Memory Systemmentioning
confidence: 99%